Biological Evaluation of [18F]AlF-NOTA-NSC-GLU as a Positron Emission Tomography Tracer for Hepatocellular Carcinoma - Lin, Liping; Xiang, Xianhong; Su, Shu; Liu, Shaoyu; Xiong, Ying; Ma, Hui; Yuan, Gongjun; Nie, Dahong; Tang, Ganghua (Frontiers in Chemistry, 2021)
Purpose: N-(2-[18F]fluoropropionyl)-L-glutamate ([18F]FPGLU) for hepatocellular carcinoma (HCC) imaging has been performed in our previous studies, but its radiosynthesis method and stability in vivo need to be improved. Hence, we evaluated the synthesis and biological properties of a simple [18F]-labeled glutamate analog, [18F]AlF-1,4,7-triazacyclononane-1,4,7-triacetic-acid-2-S-(4-isothiocyanatobenzyl)-l-glutamate ([18F]AlF-NOTA-NSC-GLU), for HCC imaging. Procedures: [18F]AlF-NOTA-NSC-GLU was synthesized via a one-step reaction sequence from NOTA-NSC-GLU. In order to investigate the imaging value of [18F]AlF-NOTA-NSC-GLU in HCC, we conducted positron emission tomography/computed tomography (PET/CT) imaging and competitive binding of [18F]AlF-NOTA-NSC-GLU in human Hep3B tumor-bearing mice. The transport mechanism of [18F]AlF-NOTA-NSC-GLU was determined by competitive inhibition and protein incorporation experiments in vitro. Results: [18F]AlF-NOTA-NSC-GLU was prepared with an overall radiochemical yield of 29.3 ± 5.6% (n = 10) without decay correction within 20 min. In vitro competitive inhibition experiments demonstrated that the Na+-dependent systems XAG-, B0+, ASC, and minor XC- were involved in the uptake of [18F]AlF-NOTA-NSC-GLU, with the Na+-dependent system XAG- possibly playing a more dominant role. Protein incorporation studies of the Hep3B human hepatoma cell line showed almost no protein incorporation. Micro-PET/CT imaging with [18F]AlF-NOTA-NSC-GLU showed good tumor-to-background contrast in Hep3B human hepatoma-bearing mouse models. After [18F]AlF-NOTA-NSC-GLU injection, the tumor-to-liver uptake ratio of [18F]AlF-NOTA-NSC-GLU was 2.06 ± 0.17 at 30 min post-injection. In vivo competitive binding experiments showed that the tumor-to-liver uptake ratio decreased with the addition of inhibitors to block the XAG system. Conclusions: We have successfully synthesized [18F]AlF-NOTA-NSC-GLU as a novel PET tracer with good radiochemical yield and high radiochemical purity. Our findings indicate that [18F]AlF-NOTA-NSC-GLU may be a potential candidate for HCC imaging. Also, a further biological evaluation is underway.